EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech in Lao People's Democratic Republic: A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, and in this case, Lao People’s Democratic Republic (PDR). This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert based at the Australian Council for Educational Research. Keywords: Ministry of Education and Sports; digital skills; training programmes; government expenditure; learning outcomes; disparities An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11118414 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1026 ZenodoArchiveConcept: 11118413
Keywords: _r:AddedByMyEducationEvidence